Application progress of liquid biopsy in gastric cancer - Ma, Xiaoting; Ou, Kai; Liu, Xiu; Yang, Lin (Frontiers in Oncology, 2022)
Gastric cancer (GC) is one of the most common malignant tumors globally. Guiding the individualized treatment of GC is the focus of research. Obtaining representative biological samples to study the biological characteristics of GC is the focus of diagnosis and treatment of GC. Liquid biopsy technology can use high-throughput sequencing technology to detect biological genetic information in blood. Compared with traditional tissue biopsy, liquid biopsy can determine the dynamic changes of tumor. As a noninvasive auxiliary diagnostic method, liquid biopsy can provide diagnostic and prognostic information concerning the progression of the disease. Liquid biopsy includes circulating tumor cells, circulating tumor DNA , circulating tumor RNA, tumor educated platelets, exosomes, and cytokines. This article describes the classification of liquid biopsy and its application value in the occurrence, development, and therapeutic efficacy of GC.